AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN MASJID MUHAJIRIN: Studi pada Masjid Muhajirin Desa Pelangki Kecamatan Batang Masumai Kabupaten Merangin (Al Dzahab, 2023)
Purpose: This study aims to determine the accountability and transparency of financial management in the Muhajirin Mosque and to determine the efforts of the mosque management in managing the financial statements of the Muhajirin mosque.Design/Methodology/ Approach: The research method used in this study is descriptive using a qualitative approach. Methods of data collection is done by using the technique of Observation, Interview and Documentation.findings: Accountability and Transparency at the Muhajirin Mosque is already responsible and transparent in its financial management. In terms of financial management, it is still simple and has not implemented PSAK 45.Research Implications: The financial statements of the Muhajirin Mosque are still very simple and have not implemented PSAK 45 because they are motivated by inappropriate education and the lack of knowledge of mosque administrators in processing financial reports of Muhajirin mosques.